Zoned in or zoned out? Investigating immersion in slot machine gambling using mobile eye‐tracking. (22nd January 2020) - Murch, W. Spencer; Limbrick‐Oldfield, Eve H.; Ferrari, Mario A.; MacDonald, Kent I.; Fooken, Jolande; Cherkasova, Mariya V.; Spering, Miriam; Clark, Luke
Abstract: Background and Aims: Immersion during slot machine gambling has been linked to disordered gambling. Current conceptualizations of immersion (namely dissociation, flow and the machine zone) make contrasting predictions as to whether gamblers are captivated by the game per se ('zoned in') or motivated by the escape that immersion provides ('zoned out'). We examined whether selected eye‐movement metrics can distinguish between these predictions. Design and Setting: Pre‐registered, correlational analysis in a laboratory setting. Participants gambled on a genuine slot machine for 20 minutes while wearing eye‐tracking glasses. Participants: Fifty‐three adult slot machine gamblers who were not high‐risk problem gamblers. Measurements: We examined self‐reported immersion during the gambling session and eye movements at different areas of the slot machine screen (the reels, the credit window, etc.). We further explored these variables' relationships with saccade count and amplitude. Findings: The ratio of dwell time on the game's credit window relative to the game's reels was positively associated with immersion ( t (51) = 1.68, P = 0.049 one‐tailed, R 2 = 0.05). Follow‐up analyses described event‐related changes in these patterns following different spin outcomes. Conclusions: Immersion while gambling on a slot machine appears to be associated with active scanning of the game and a focus on the game's credit window. These results are more consistent with a 'zoned in' account of immersion aligned with flow theory than a 'zoned out' account based on escape.